2016
DOI: 10.5194/gmd-9-1977-2016
|View full text |Cite
|
Sign up to set email alerts
|

LAKE 2.0: a model for temperature, methane, carbon dioxide and oxygen dynamics in lakes

Abstract: Abstract. A one-dimensional (1-D) model for an enclosed basin (lake) is presented, which reproduces temperature, horizontal velocities, oxygen, carbon dioxide and methane in the basin. All prognostic variables are treated in a unified manner via a generic 1-D transport equation for horizontally averaged property. A water body interacts with underlying sediments. These sediments are represented by a set of vertical columns with heat, moisture and CH 4 transport inside. The model is validated vs. a comprehensive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 72 publications
0
126
0
5
Order By: Relevance
“…CH 4 accumulation near the bottom usually happens in the anoxic conditions in late autumn (Stepanenko et al, 2016). CH 4 concentration at 11 m depth was still three times lower than the maximum concentration found in Stepanenko et al (2016) in late September and 2 times lower than found at 12 m depth in Miettinen et al (2015) in September. A clear increase in CH 4 surface water concentration is seen on 23 September due to upwelling and concentration up to 0.19 mmol m −3 was measured with the automatic system on 24 September.…”
Section: Environmental Conditions and Water Column Temperaturementioning
confidence: 82%
See 2 more Smart Citations
“…CH 4 accumulation near the bottom usually happens in the anoxic conditions in late autumn (Stepanenko et al, 2016). CH 4 concentration at 11 m depth was still three times lower than the maximum concentration found in Stepanenko et al (2016) in late September and 2 times lower than found at 12 m depth in Miettinen et al (2015) in September. A clear increase in CH 4 surface water concentration is seen on 23 September due to upwelling and concentration up to 0.19 mmol m −3 was measured with the automatic system on 24 September.…”
Section: Environmental Conditions and Water Column Temperaturementioning
confidence: 82%
“…CO 2 concentration at 11 m depth was 10 times higher than at the surface and comparable to those measured in Miettinen et al (2015) at 12 m depth. Diel variation observed in CO 2 concentration at 11 m could be caused by either lake-side cooling and convection or by internal waves (Stepanenko et al, 2016).…”
Section: Co 2 Concentration Profilementioning
confidence: 99%
See 1 more Smart Citation
“…The weightings provided by each layer to the sediment are based on the relative depth overlap of a layer with the depth range of the sediment zone. This approach makes the model suitable for long-term assessments of wetland, lake and reservoir 5 biogeochemical budgets, including for C, N and other attribute balances as required (Stepanenko et al, 2016). Secondly, the water quality modules feed back to GLM properties related to the water and/or heat balance.…”
Section: Dynamic Coupling With Biogeochemical and Ecological Model LImentioning
confidence: 99%
“…The algorithms and assumptions applied by these models vary greatly, as does their complexity, which ranges from simple box models to intricate three-dimensional models (Stepanenko et al, 2016;Wang et al, 2016;Ji, 2008;Hodges et al, 2000). For climate change studies, long-time lake simulations are needed, often utilizing vertical one-dimensional (1-D) models (Wood et al, 2016;Butcher et al, 2015;Komatsu et al, 2007;Hostetler and Small, 1999).…”
Section: Numerical Modellingmentioning
confidence: 99%